Digital media and its impact on Iraqi youth adopting Western culture - Dr. Muthana Ibrahim Jaber Altalqany; Dr. Ayad abbas hassan; Mazen Amer Abdel Razzaq Al Hamami (Genius Journals, 2026)
The world today lives in the digital age and digital communication technology has developed amazingly in recent years and Western countries are the ones that dominate and control this technology. Therefore, this study aimed to identify "the impact of digital media on Iraqi youth in adopting Western culture." The researcher adopted the descriptive analytical approach to achieve the research goal and prepared a questionnaire form consisting of (27) twenty-seven paragraphs as a research tool. After it was approved by experts, it was applied to a sample of (300) three hundred students from the University of Kufa
Keywords: consisting; questionnaire; paragraphs